ANALISIS PENGGUNAAN IDEOLOGI AKUN-AKUN DAKWAH GARIS LUCU PADA PLATFORM TWITTER - Armanda Prastiyan Pratama (Jurnal Penelitian Ilmiah INTAJ, 2023)
The Garis Lucu accounts use a comedic style in almost all of their content, with the aim of reducing radicalization while at the same time demonstrating that every religious teaching can apply tolerance towards adherents of other religions. This has attracted the interest of researchers to find out the ideology used by these Garis Lucu accounts. The Twitter platform was chosen, because these accounts use Twitter more often to share their content. This is evidenced by the content uploaded by these accounts on other social media platforms, many of which originate from content previously uploaded by the Garis Lucu accounts on the Twitter platform (repost). This study aims to determine the type of ideology used by the Garis Lucu accounts and their application to uploaded content. It uses a qualitative approach with descriptive methods. Da'wah can be done in various ways, one of which is by using a touch of comedy and tolerance, as is done by the Garis Lucu da'wah accounts. These accounts show that da'wah can be carried out in simple words that can be easily understood, then by using open ideology, these accounts can comfortably interact with each other to show the values of tolerance that must be possessed between religious communities.